Vitamin - D level and severity of COVID-19 among the Admitted Patients in a COVID Dedicated Tertiary Care Hospital - An Prospective Study - Miah, Md Titu; Yasmin, Rubina; Haque, Md Monjurul; Azad, Nazim Al; Parveen, Rahnuma; Paul, Nandita; Habib, Rahat Bin; Deb, Sudip Ranjan; Haque, Md Ahsanul; Barman, Tushar Kanti (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background The impact of vitamin D on COVID-19 infection has been much discussed recently. Our aim was to evaluate the association between baseline serum 25(OH)D with severity of COVID-19. Method This was an prospective study, where 174 COVID- 19 in-patients of an academic hospital in an urban setting were enrolled from Aug, 2020 to Oct, 2020. After detailed clinical history taking and examination, patients were divided into mild, moderate, severe and critical categories. Vitamin D level was measured. Relation between level of vitamin D and disease severity was determined. Result Mean age of the study population was 52.01 years. 13% mild, 22.99% moderate, 26.44% severe and 3.45% were critical cases. 76% of the patients had vitamin D deficiency. No statistical significance between the level of vitamin D and disease severity was seen (p= 0.430). Conclusion Our study revealed there is no correlation between vitamin D deficiency and severity of COVID-19. J Bangladesh Coll Phys Surg 2022; 40: 166-170